2020
DOI: 10.1177/1477153520958454
|View full text |Cite
|
Sign up to set email alerts
|

Review of road surface photometry methods and devices – Proposal for new measurement geometries

Abstract: Specifications concerning road lighting and photometry of road surfaces were established more than 50 years ago. Road lighting design and road marking visibility were developed for vehicle driving. The observation distance defined by standards corresponds to interurban applications; however, within Europe these areas do not tend to be lit. The objective of the SURFACE project is to propose new geometries for the photometric characterisation of pavements, both adapted to different urban travel modes and new lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…After a detailed comparison, we observed that the main difference between the two standards is the observer positioning, which, as other papers suggest [16], can have a significant influence on the average luminance value due to the reflection properties of the asphalt [17][18][19]. Considering this, the second section of the paper presents an overview of the differences from the two standards and a case study, for three particular roads in which the average luminance values are compared when calculated with the same input data, but as per the two standards.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…After a detailed comparison, we observed that the main difference between the two standards is the observer positioning, which, as other papers suggest [16], can have a significant influence on the average luminance value due to the reflection properties of the asphalt [17][18][19]. Considering this, the second section of the paper presents an overview of the differences from the two standards and a case study, for three particular roads in which the average luminance values are compared when calculated with the same input data, but as per the two standards.…”
Section: Introductionsupporting
confidence: 69%
“…According to [16], changing the angle of observation directly affects the average luminance on a road. They also conclude that the European standard needs to be updated in order to add extra angles of observation according to the type of road.…”
Section: The Influence Of Longitudinal Observer Position In Luminance Calculationmentioning
confidence: 99%
“…To study the spatial heterogeneity of pavement reflection properties, photometric evaluation was performed on-site with a portable measurement device named COLUROUTE [27,36] (picture on the left in Figure 4), which complies with the specifications of the CIE [13]. The luminance coefficients of the road surface are measured on-site, in daylight, and without sampling.…”
Section: On-site Measurement Of Road Photometrymentioning
confidence: 99%
“…This implies characterizing the pavement reflection properties from angles other than the conventional 1 • . It also implies adapting the methodology for dimensioning and measuring the performance of a lighting installation by systematizing the use of luminance [27,28]. For the classical calculations at 1 • , the observer is fixed and located 60 m in front of the calculation zone [9,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation